The impact of the COVID-19 pandemic on European police officers: Stress, demands, and coping resources. (January 2021) - Frenkel, Marie Ottilie; Giessing, Laura; Egger-Lampl, Sebastian; Hutter, Vana; Oudejans, Raoul R.D.; Kleygrewe, Lisanne; Jaspaert, Emma; Plessner, Henning
Abstract: Purpose: Facing the COVID-19 pandemic, police officers are confronted with various novel challenges, which might place additional strain on officers. This mixed-method study investigated officers' strain over a three-month-period after the lockdown. Methods: In an online survey, 2567 police officers (77% male) from Austria, Germany, Switzerland, the Netherlands, and Spain participated at three measurement points per country in spring, 2020. Three-level growth curve models assessed changes in strain and its relation to stressor appraisal, emotion regulation, and preparedness through training. To add context to the findings, free response answers about officers' main tasks, stressors, and crisis measures were coded inductively. Results: On average, officers seemed to tolerate the pandemic with slight decreases in strain over time. Despite substantial variance between countries, 66% of the variance occurred between individuals. Sex, work experience, stressor appraisal, emotion regulation, and preparedness significantly predicted strain. Risk of infection and deficient communication emerged as main stressors. Officers' reports allowed to derive implications for governmental, organizational, and individual coping strategies during pandemics. Conclusion: Preparing for a pandemic requires three primary paths: 1) enacting unambiguous laws and increasing public compliance through media communication, 2) being logistically prepared, and 3) improving stress regulation skills in police training. Highlights: The mixed-method study assessed officers' strain over ten weeks after the lockdown. On average, officers seemed to tolerate the strain with slight decreases over time. Demography and coping factors explained variance between countries and individuals. Risk of infection and deficient communication emerged as main stressors. Crisis management requires clear laws, logistic precautions, and individual coping.